Bank Locker Security with Fingerprint and Image Capture - V. Hindumati,; M. Sushmitha,; M.Yoshitha,; R. Venkata Harika,; A. Sri Vaishnavi, (Journal of Electronic Design Engineering, 2019)
The secure fingerprint based bank locker system is an enhancement to the traditional bank locker system that uses keys. The fingerprint authenticated bank locker system is safe as well as easy to use and maintain. The system uses fingerprint sensing and image capture. This system scans the fingerprint and also capture the image of user and compares with registered customer image. If match is not found with existing image of the particular user, then it sends the message to the concern bank manager and the customer. Also, the buzzer is used to know about the unauthorized person to the bank manager immediately. If it match with both fingerprint and image then the locker opens.